Making a difference through presentations: Let’s speak, communicate, and connect! - Furumizu, Chihiro; Ichihashi, Yasunori (Frontiers in Education, 2025)
In our personal and professional lives, we have numerous opportunities to communicate our ideas to others. Therefore, the importance of presentation goes beyond academic success. However, efforts to improve presentation skills may be hampered by a variety of barriers, both personal and social, creating educational challenges. For example, the importance of presentation and communication skills is widely recognized among professionals in western countries, but this is not the case in some other countries. Overcoming these barriers would improve presentation skills and help individuals from diverse backgrounds effectively communicate their ideas. This would raise the visibility of underrepresented people, thereby increasing their recognition in both academic and non-academic settings, making the community as a whole more inclusive. Toward these goals, a pilot training workshop on presentations titled “Let’s Speak, Communicate, and Connect!” was held at the annual meeting of the Japanese Society of Plant Physiologists in March 2024. The participants expressed great interest in improving their presentation styles and receiving feedback, highlighting the need for such training programs. In the post-workshop survey, 16 of the 17 respondents indicated that the workshop helped them improve their presentations. These results suggest that the workshop lowered barriers to presentation and allowed for improvement. Improved presentations can also benefit outreach efforts. Altogether, we believe that cross-community support for improving presentation skills not only helps members in their personal development but also contributes to strengthening connections between the academic community and society.